INFLUENCES OF VEGETATION STRUCTURE (VS) ON METEOROLOGICAL PARAMETERS IN BUILT ENVIRONMENT; A FIELDWORK STUDY - Noorazlina Kamarulzaman; Mazran Ismail; Hazril Sherney Basher; Asmat Ismail, (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
Vegetation plays a crucial role in establishing a comfortable thermal environment by regulating temperature, humidity, and wind velocity. It is a well-documented that the Vegetation Structure (VS) variables, including height, density, leaf colour and size, canopy, density can have a significant impact on the microclimate inside and around the plants. However, the correlation between the different vegetation structures around residential buildings and the meteorological conditions inside and outside remains unclear. In this paper, an experimental investigation was carried out to determine the effect of VS on residential buildings’ microclimate. Parameters of meteorological were measured in and around two Case Study (CS1 & CS2) which are single story buildings located in Perak, Malaysia. Five days of meteorological data were collected using a Thermal Microclimate Datalogger (HD32.1 Delta Ohm) and an Indoor Air Quality Datalogger (HD37AB1347 Delta Ohm) to measure temperature (oC), relative humidity (%), and air velocity (m/s). Both case study's VS variables were measured and then thoroughly examined to determine the potential of VS in generating a pleasant thermal environment. This research compares and discusses VS and meteorological parameters measured within and outside of the case study buildings. The results were analyzed in three Quartile: Q1 from 7:30 a.m. to 11:00 a.m., Q2 from 11.15 a.m. to 2:30 p.m., and Q3 from 2:45 p.m. to 6:00 p.m. In Q1, CS1 shows the highest outdoor-indoor temperature difference of 2.31℃ compared to 2.02oC for CS2. In contrast, CS2 recorded the highest ambient temperature differences of 1.35℃ and 2.73oC in Q2 and Q3, respectively compared to CS1; 1.27oC and 1.19℃. Overall, vegetation structure can have a significant impact on meteorological parameters, which can in turn influence indoor and outdoor thermal performance.